The effect of blockage on tidal turbine rotor design and performance. (September 2015) - Schluntz, J.; Willden, R.H.J.
Abstract: The performance-enhancing effects of closely packing tidal turbines in single row arrays (tidal fences) are evaluated in this computational study. Infinitely long tidal fences are simulated with a range of lateral rotor spacings using a blade element momentum method embedded in a Reynolds averaged Navier–Stokes solver (RANS-BEM). First, a rotor design tool is applied to determine a hydrodynamically optimal rotor design for each lateral spacing. In the RANS-BEM method, the effect of blockage (the ratio of rotor swept area to channel cross-sectional area) on rotor optimization is accounted for. Increased blockage is found to result in increased optimal solidity and decreased optimal pitch. Next, each rotor design is simulated in its design spacing as well as several off-design spacings. The resulting power coefficient is largest when the rotor optimized for the highest blockage case operates in the array with the closest lateral spacing. Further, although a rotor's performance is improved through operation at a blockage higher than its design point, it still exhibits inferior performance relative to a rotor designed for that higher blockage. The results indicate that blockage must be considered in the rotor design process if the optimal rotor efficiency for a given spacing is to be achieved. Highlights: We design tidal turbine rotors for blocked flow conditions using a RANS-BEM model. Designing rotors for operating blockage conditions improves the power coefficient. Rotors designed for high blockage conditions require increased solidity. Rotors designed for high blockage perform poorly in unblocked flow conditions.